The Epistemology of Ibn Arabi and Al-Ghazali's Sufism: A Comparative Study of the Source and Validity of Spiritual Knowledge - Suparna, Ahmad; Rohanda, Rohanda; Kodir, Abdul (Syifa al-Qulub : Jurnal Studi Psikoterapi Sufistik, 2025)
The epistemology of Sufism, as a bridge between rational knowledge and spiritual experience in Islam, has long fascinated Muslim thinkers. This research reveals the complex layers of thought of Ibn Arabi and Al-Ghazali, two Sufi figures whose thoughts have resonated throughout the centuries. Through in-depth analysis of their monumental works, this study reveals how these two figures navigated the sea of ma'rifah (intuitive knowledge) on different ships but headed to the same port. Al-Ghazali, with his kashf compass, sailed carefully between the currents of the Shari'a and reality, while Ibn Arabi, with his Wahdat al-Wujud sails, sailed a wider horizon, embracing the winds of Greek and Bathiniyah philosophy. This research not only maps their spiritual routes, but also explores how the knowledge maps they drew are still relevant in the navigation of contemporary spirituality, offering a new compass for seekers of meaning in the modern era.